The Impact of Knowledge Provision and Medication Consultation for Type 2 Diabetes Patients Uncontrolled by Pharmacists at the Community Medical Center, Buriram Hospital Branch 1, Buriram Province - Pathumwiwattana, Wannee (Journal of the office of disease prevention and control 9 Nakhon Ratchasima, 2023)
A quasi-experimental study was conducted following a routine research design, measuring pre-test and post-test outcomes in one group of participants. The study aimed to compare diabetes knowledge, self-care behavior, drug consumption behavior, and HbA1C levels in type 2 diabetes mellitus patients before and after a session of drug education and counseling provided by pharmacists. The participants included 35 uncontrolled type 2 diabetes mellitus patients who had not previously sought medical assistance at the community medical center of Buriram Hospital 1 in Buriram province. Data collection involved a pre-intervention assessment, followed by a post-intervention assessment after a duration of 12 weeks, utilizing a questionnaire and blood tests (HbA1C). The data were analyzed using frequency, percentage, mean, and standard deviation. The mean difference between before and after the experiment was tested using the Paired Sample t-test. The findings indicated that mean scores of diabetes knowledge, self-care behavior, and patients' drug utilization significantly increased after receiving education and drug counseling (p < 0.001). Furthermore, blood sugar levels (HbA1C) decreased significantly (p < 0.001). Thus, drug education and counseling for patients with uncontrolled type 2 diabetes mellitus should serve as a guideline to enhance self-care proficiency for diabetes and other chronic conditions patients. Moreover, it is recommended to conduct follow-up sessions continuously at 3 weeks, 6 weeks, and 1 year to evaluate behavioral changes and blood sugar levels.